1999
DOI: 10.1055/s-2007-1011091
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin E1zur Prophylaxe kontrastmittelinduzierter Nierenfunktionsstörungen

Abstract: Our results suggest that intravenously administered PGE1 may be efficient in preventing CM-induced renal dysfunction in patients with renal impairment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…A total of 32,399 studies were excluded after remove duplication the most common reasons for exclusions after full examination included observational methodology; different outcome measures, inadequate definition of CI-AKI; unclear evidence of randomization; old studies that did not comply with eligibility criteria for more than one reason [ 216 – 279 ]. The twelve studies published in a non-English language included those from centers in Germany [ 280 , 281 ], China [ 282 – 287 ], Spain [ 288 ], France [ 289 ], Turkey [ 290 ] and Italy [ 291 ]. Eight further potentially suitable studies were identified in abstract form only, but were excluded as no full-text article could be identified [ 292 – 299 ].…”
Section: Resultsmentioning
confidence: 99%
“…A total of 32,399 studies were excluded after remove duplication the most common reasons for exclusions after full examination included observational methodology; different outcome measures, inadequate definition of CI-AKI; unclear evidence of randomization; old studies that did not comply with eligibility criteria for more than one reason [ 216 – 279 ]. The twelve studies published in a non-English language included those from centers in Germany [ 280 , 281 ], China [ 282 – 287 ], Spain [ 288 ], France [ 289 ], Turkey [ 290 ] and Italy [ 291 ]. Eight further potentially suitable studies were identified in abstract form only, but were excluded as no full-text article could be identified [ 292 – 299 ].…”
Section: Resultsmentioning
confidence: 99%